Tetrandrine Suppresses Cancer Angiogenesis and Metastasis in 4T1 Tumor Bearing Mice. (25th May 2013) - Gao, Jian-Li; Ji, Xing; He, Tong-Chuan; Zhang, Qi; He, Kai; Zhao, Yan; Chen, Su-Hong; Lv, Gui-Yuan
Abstract : Metastasis remains the most deadly aspect of cancer and still evades direct treatment. Thus, there is a great need to develop new treatment regimens to suppress tumor cells that have escaped surgical removal or that may have already disseminated. We have found that tetrandrine (TET) exhibits anticolon cancer activity. Here, we investigate the inhibition effect of TET to breast cancer metastasis, angiogenesis and its molecular basis underlying TET's anticancer activity. We compare TET with chemotherapy drug doxorubicin in 4T1 tumor bearing BALB/c mice model and find that TET exhibits an anticancer metastatic and antiangiogenic activities better than those of doxorubicin. The lung metastatic sites were decreased by TET, which is confirmed by bioluminescence imaging in vivo . On the other hand, laser doppler perfusion imaging (LDI) was used for measuring the blood flow of tumor in 4T1-tumor bearing mice. As a result, the local blood perfusion of tumor was markedly decreased by TET after 3 weeks. Mechanistically, TET treatment leads to a decrease in p-ERK level and an increase in NF- κ B levels in HUVECs. TET also regulated metastatic and angiogenic related proteins, including vascular endothelial growth factor, hypoxia-inducible factor-1 α, integrin β 5, endothelial cell specific molecule-1, and intercellular adhesion molecule-1 in vivo .